Sediment core data (organic carbon, dry bulk density, grain size, radionuclide) from the Western Irish Sea Mud Belt June 2022 - Hannah C Muir; David G Reading; Phillip E Warwick; Kate Peel; Claire Evans (PANGAEA, 2025)
Sediment cores were collected from the Western Irish Sea Mud Belt (Isle of Man territorial water) using a UWITEC gravity corer (height = 120 cm; internal diameter = 9 cm) launched from the Barrule fisheries enforcement vessel (Isle of Man Government) in June 2022, as part of the Manx Blue Carbon Project. Latitude and longitude for each core were recorded using a GPS unit onboard the vessel. Water depth at each site was recorded using the research vessel depth sounder when the corer reached the seabed. After suspended sediment settled at the surface of the core, overlying water was drained to limit sediment–water mixing during transport. The cores were labelled with unique Site ID codes and the time and date of retrieval were recorded. The cores were stored at temperatures below 5°C to preserve their integrity and transported upright to the National Oceanography Centre, Southampton, where all subsequent laboratory analyses were performed. The cores were analyzed for organic carbon, dry bulk density, grain size and radionuclides.